Comparing Thermal Regime Stages along a Small Yakutian Fluvial Valley with Point Scale Measurements, Thermal Modeling, and Near Surface Geophysics - Léger, Emmanuel; Saintenoy, Albane; Grenier, Christophe; Séjourné, Antoine; Pohl, Eric; Bouchard, Frédéric; Pessel, Marc; Bazhin, Kirill; Danilov, Kencheeri; Costard, François; Mugler, Claude; Fedorov, Alexander; et al. (Remote sensing (Basel, Switzerland), 2023)
Arctic regions are highly impacted by the global temperature rising and its consequences and influences on the thermo-hydro processes and their feedbacks. Theses processes are especially not very well understood in the context of river–permafrost interactions and permafrost degradation. This paper focuses on the thermal characterization of a river–valley system in a continuous permafrost area (Syrdakh, Yakutia, Eastern Siberia) that is subject to intense thawing, with major consequences on water resources and quality. We investigated this Yakutian area through two transects crossing the river using classical tools such as in–situ temperature measurements, direct active layer thickness estimations, unscrewed aerial vehicle (UAV) imagery, heat transfer numerical experiments, Ground-Penetrating Radar (GPR), and Electrical Resistivity Tomography (ERT). Of these two transects, one was closely investigated with a long-term temperature time series from 2012 to 2018, while both of them were surveyed by geophysical and UAV data acquisition in 2017 and 2018. Thermodynamical numerical simulations were run based on the long-term temperature series and are in agreement with river thermal influence on permafrost and active layer extensions retrieved from GPR and ERT profiles. An electrical resistivity-temperature relationship highlights the predominant role of water in such a complicated system and paves the way to coupled thermo-hydro-geophysical modeling for understanding permafrost–river system evolution.